Blue light conversion resin, preparation method and application thereof
The fluorescence intensity and grafting of the blue-light resin are improved by chemical bonding of N-allyl-4-methoxy-1,8-naphthimide on the polyolefin and the addition of appropriate additives. Efficiency solves the problem of insufficient fluorescence intensity in the prior art and is suitable for a variety of application fields.
Patent Information
- Application Number
- CN202411269444.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-27
AI Technical Summary
The fluorescence intensity of the prior art transient blue light resin is not high and the free radical distribution is uneven, resulting in a low graft rate, and the fluorescence intensity of the transient blue light resin is at a maximum value of 410 nm. No more than 3000 a.u.
N-allyl-4-methoxy-1,8-naphthalimide is used to carry out chemical bonding and grafting on polyolefins, and the blue-ray resin is prepared by melt extrusion molding to improve the grafting rate and fluorescence intensity. Silane coupling agent, polycarbodiimide and polyethylene glycol were added to adjust the UV light transmittance.
It significantly improves the fluorescence intensity of blue-ray resin in the wavelength range of 400-450nm, reaching 105a.u. and above, improves grafting efficiency, and adjusts the ultraviolet light transmittance. It is suitable for light-transforming films, photovoltaics and fluorescent materials. .
Smart Images

Figure CN119192482A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of light conversion materials and relates to a blue light conversion resin, a preparation method and application thereof. Background Art
[0002] Light-converting materials have great application prospects in agriculture, photovoltaics and other fields. By grafting organic light-converting materials into polymers, a stable light-converting resin can be formed, which has stable performance and is easy to process. Prior art CN104387534A discloses that 1,8-naphthalimide compounds are grafted onto polyethylene to prepare a blue light-converting resin, which can be used as a light-converting agricultural film. The polyethylene is irradiated in advance, and then N-allyl-4-methoxy-1,8-naphthalimide is added for grafting reaction. However, this technology has the following shortcomings: (1) Polyethylene pre-irradiation can only generate free radicals on the polyethylene surface or near the surface. The free radicals are unevenly distributed and insufficient, resulting in a low grafting rate of N-allyl-4-methoxy-1,8-naphthalimide. N-allyl-4-methoxy-1,8-naphthalimide is mainly grafted on the surface of polyethylene; (2) Polyethylene pre-irradiation generates free radicals, and the next reaction must be carried out in a short time, otherwise the free radicals will gradually quench; (3) The fluorescence intensity of the blue light-converting resin is not high, with the highest fluorescence intensity at 410nm, but the fluorescence intensity does not exceed 3000a.u. (10 3 level).
[0003] Therefore, it is necessary to conduct further research on the above-mentioned prior art to improve the performance of blue light conversion resin, such as increasing the fluorescence intensity. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a blue light conversion resin, a preparation method and application thereof.
[0005] The technical solution of the present invention is as follows:
[0006] A blue light conversion resin, wherein the blue light conversion resin is N-allyl-4-methoxy-1,8-naphthalimide chemically bonded and grafted on polyolefin;
[0007] The grafting rate of the N-allyl-4-methoxy-1,8-naphthalimide on the blue light conversion resin is 0.1-0.5wt%;
[0008] The grafting rate is tested using an elementar vario EL cube organic element analyzer;
[0009] The maximum fluorescence intensity of the blue light conversion resin in the wavelength range of 400-450nm is not less than 10 5 au;
[0010] The fluorescence intensity was tested using the FLS1000 steady-state transient fluorescence spectrometer from Edinburgh Instruments, with an excitation wavelength of 380 nm, an excitation slit of 0.7 nm, an emission slit of 0.7 nm, detection every 1 nm, and a wavelength range of 390-800 nm.
[0011] Preferably, the melt index of the polyolefin is 0.1-40 g / 10 min.
[0012] Preferably, the ultraviolet light transmittance of the blue light converting resin within the wavelength range of 280-380 nm does not exceed 20%.
[0013] Preferably, the grafting rate is 0.15-0.5 wt %.
[0014] Preferably, the blue light conversion resin further contains 0.3-1% by weight of a silane coupling agent based on the weight of the blue light conversion resin.
[0015] Preferably, the blue light conversion resin further contains polycarbodiimide accounting for 0.3-1% of the weight of the blue light conversion resin, and the ultraviolet light transmittance of the blue light conversion resin within the wavelength range of 280-380nm does not exceed 5%.
[0016] Preferably, the blue light conversion resin further contains polyethylene glycol accounting for 0.5-2% by weight of the blue light conversion resin, and the ultraviolet light transmittance of the blue light conversion resin within the wavelength range of 280-380nm does not exceed 15%.
[0017] A method for preparing a blue light-converting resin as described in any of the above technical solutions, comprising uniformly mixing the N-allyl-4-methoxy-1,8-naphthalimide, the polyolefin and the free radical thermal initiator, adding the mixture to a screw extruder for melt extrusion molding, and obtaining the blue light-converting resin.
[0018] Preferably, the melting section temperature of the melt extrusion molding is 140-230°C, and the die temperature is 150-200°C.
[0019] An application of the blue light conversion resin described in any of the above technical solutions or the blue light conversion resin obtained by the preparation method of the blue light conversion resin described in any of the above technical solutions is applied to light conversion films, photovoltaic and fluorescent materials.
[0020] The beneficial effects of the present invention are:
[0021] (1) The blue light-converting resin of the present invention has a high fluorescence intensity in the wavelength range of 400-450nm, which can reach 10 5 au and above, can even reach 10 6 au and above, which is 2 or even 3 orders of magnitude higher than that recorded in the prior art;
[0022] (2) By further adding other materials to the blue light conversion resin of the present invention, the performance of the blue light conversion resin can be adjusted, such as the ultraviolet light transmittance within the wavelength range of 280-380nm.
[0023] (3) The blue light-converting resin of the present invention can be directly prepared by melt grafting, which is easy to operate and has a high grafting efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the fluorescence emission spectrum of the blue light conversion resin of Example 1.
[0025] Figure 2 This is the ultraviolet-visible light transmission spectrum of the blue light conversion resin of Example 1.
[0026] Figure 3 This is the fluorescence emission spectrum of the blue light conversion resin of Example 3.
[0027] Figure 4 This is the ultraviolet-visible light transmission spectrum of the blue light conversion resin of Example 3.
[0028] Figure 5 This is the fluorescence emission spectrum of the blue light conversion resin of Example 4.
[0029] Figure 6 This is the ultraviolet-visible light transmission spectrum of the blue light conversion resin of Example 4.
[0030] Figure 7 This is the fluorescence emission spectrum of the blue light conversion resin of Example 5.
[0031] Figure 8 This is the ultraviolet-visible light transmission spectrum of the blue light conversion resin of Example 5. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further illustrated and described below through specific implementation methods.
[0033] In order to solve the problems of low fluorescence intensity of blue light conversion resin in the prior art, on the one hand, the present invention provides a blue light conversion resin, wherein the blue light conversion resin is N-allyl-4-methoxy-1,8-naphthalimide chemically bonded and grafted on polyolefin;
[0034] N-allyl-4-methoxy-1,8-naphthalimide has a structure as shown in the following formula (1), and has the characteristics of high fluorescence quantum yield, large Stokes shift, good light, heat and chemical stability, etc. In addition, N-allyl-4-methoxy-1,8-naphthalimide contains an allyl group in its molecular structure, which can undergo graft polymerization under the action of free radicals.
[0035]
[0036] In the present invention, the grafting rate of N-allyl-4-methoxy-1,8-naphthalimide on the blue light conversion resin is 0.1-0.5wt%; the grafting rate refers to the percentage of grafted N-allyl-4-methoxy-1,8-naphthalimide in the weight of the blue light conversion resin.
[0037] In the present invention, the grafting rate is tested by using an elementar vario EL cube organic element analyzer to test the content of N element in the blue light conversion resin, and then the grafting rate of N-allyl-4-methoxy-1,8-naphthalimide is calculated;
[0038] The maximum fluorescence intensity of the blue light-converting resin in the wavelength range of 400-450nm is not less than 10 5 au, further, the highest fluorescence intensity is not less than 2×10 5 au, or further, the maximum fluorescence intensity is not less than 3×10 5 au;
[0039] In the present invention, the maximum fluorescence intensity refers to the maximum fluorescence intensity within the wavelength range of 400-450nm, and the maximum fluorescence intensity corresponds to a specific wavelength, and the specific wavelength can be 407nm, 415nm, 422nm, 435nm, etc. The fluorescence intensity is tested using the FLS1000 steady-state transient fluorescence spectrometer of Edinburgh Instruments, with an excitation wavelength of 380nm, an excitation slit of 0.7nm, an emission slit of 0.7nm, and detection every 1nm, with a wavelength range of 390-800nm.
[0040] Polyolefin (POE) is a homopolymer of ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene and 4-methyl-1-pentene or a copolymer of two or more thereof. In a preferred embodiment of the present invention, the melt index of the polyolefin can be 0.1-40g / 10min. The melt index has different test conditions according to the main cost of the polyolefin. For example, if POE uses polyethylene as the main component, the test condition of the melt index is (190°C, 2.16Kg). If POE uses polypropylene as the main component, the test condition of the melt index is (230°C, 2.16Kg), which is well known to those skilled in the art.
[0041] In a preferred embodiment of the present invention, the ultraviolet transmittance of the blue light conversion resin in the wavelength range of 280-380nm does not exceed 20%. For example, the ultraviolet transmittance of the blue light conversion resin in the wavelength range of 280-380nm can be any value of 5%, 7%, 8%, 10%, 12%, 15%, 16%, 17%, 18%, 19%, 20%, etc., without special restrictions.
[0042] In a preferred embodiment of the present invention, the grafting rate is 0.15-0.5wt%. For example, the grafting rate can be any value in 0.15wt%, 0.18wt%, 0.2wt%, 0.22wt%, 0.25wt%, 0.27wt%, 0.3wt%, 0.32wt%, 0.35wt%, 0.38wt%, 0.4wt%, 0.42wt%, 0.45wt%, 0.48wt%, 0.5wt%, etc., without particular limitation. Further preferably, the grafting rate is 0.22-0.35wt%.
[0043] In a preferred embodiment of the present invention, the blue light conversion resin also contains a silane coupling agent accounting for 0.3-1% of the weight of the blue light conversion resin. The silane coupling agent has an alkoxysilyl group that can be hydrolyzed and react with groups such as hydroxyl groups. Therefore, in the present invention, the addition of a silane coupling agent to the blue light conversion resin can improve the binding force of the blue light conversion resin to some substrates (such as glass, steel, etc.). In the present invention, there is no particular limitation on the silane coupling agent, which can be directly obtained from commercially available products. For example, it can be KH-570, KH-792, KH-791, KH-550, KH-560, KH-540. For example, the silane coupling agent can account for any value of 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc., by weight of the blue light conversion resin, without any particular limitation.
[0044] In a preferred embodiment of the present invention, the blue light conversion resin also contains polycarbodiimide accounting for 0.3-1% of the weight of the blue light conversion resin, and the ultraviolet light transmittance of the blue light conversion resin in the wavelength range of 280-380nm does not exceed 5%. Polycarbodiimide has an anti-hydrolysis effect and is a commonly used anti-hydrolysis agent that can be directly obtained from the market, which can improve the stability of the blue light conversion resin in a humid environment. Moreover, the inventors found that the addition of polycarbodiimide significantly reduced the ultraviolet light transmittance of the blue light conversion resin in the wavelength range of 280-380nm compared to the absence of polycarbodiimide. For example, the ultraviolet light transmittance of the blue light conversion resin in the wavelength range of 280-380nm can be any value of 1%, 2%, 3%, 4%, 5%, etc., without special restrictions. For example, the weight of polycarbodiimide in the blue light conversion resin can be any value among 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc., without any particular limitation.
[0045] In a preferred embodiment of the present invention, the blue light conversion resin also contains 0.5-2% polyethylene glycol by weight of the blue light conversion resin, and the ultraviolet light transmittance of the blue light conversion resin in the wavelength range of 280-380nm does not exceed 15%. The addition of polyethylene glycol can promote the dispersibility of N-allyl-4-methoxy-1,8-naphthalimide in polyolefins, and can also improve the hydrophilicity of the blue light conversion resin. In the present invention, the number average molecular weight of polyethylene glycol is not particularly limited, and can be 400-10000, or further, the number average molecular weight can be 1200-8000, such as PEG-2000 (2000 represents the number average molecular weight of PEG). In the present invention, the polyethylene glycol can account for any value of 0.5%, 0.7%, 0.8%, 1%, 1.2%, 1.3%, 1.5%, 1.6%, 1.8%, 2%, etc., without special restrictions.
[0046] On the other hand, the present invention proposes a method for preparing a blue light-converting resin described in any of the above technical solutions, using a melt grafting method, N-allyl-4-methoxy-1,8-naphthalimide, polyolefin and free radical thermal initiator are mixed evenly, added to a screw extruder for melt extrusion molding, and the blue light-converting resin is obtained. In the present invention, the melt grafting reaction method is directly adopted, and the free radical thermal initiator is decomposed into free radicals in the melting section and initiates the polymerization of N-allyl-4-methoxy-1,8-naphthalimide to polyolefin. The method is simple to operate and has high efficiency. In the present invention, the free radical thermal initiator is not particularly limited, and can be a peroxide, such as diisopropylbenzene peroxide (DCP), isopropylbenzene hydroperoxide (CHP), di-tert-butyl peroxide (DTBP), 2,5-di-tert-butyl peroxide-2,5-dimethylhexane (DHBP), benzoyl peroxide (BPO), etc.
[0047] When the raw material components also contain other raw materials (such as silane coupling agent, polycarbodiimide, polyethylene glycol, etc.), they can be added together during mixing, or added together to a twin-screw extruder after mixing for melt extrusion molding.
[0048] In a preferred embodiment of the present invention, the melting section temperature of melt extrusion molding is 140-230° C., and the die temperature is 150-200° C. The main components of the polyolefin are different, and the melting section temperature and the die temperature are also different. For example, when the polyolefin is mainly composed of polyethylene, the melting section temperature can be 140-190° C., and the die temperature can be 150-180° C. When the polyolefin is mainly composed of polypropylene, the melting section temperature can be 180-230° C., and the die temperature can be 180-200° C.
[0049] On the other hand, the present invention provides an application of a blue light conversion resin as described in any of the above technical solutions or a blue light conversion resin obtained by the preparation method of the blue light conversion resin as described in any of the above technical solutions, which is applied to light conversion films, photovoltaics and fluorescent materials. The blue light conversion resin of the present invention has a high fluorescence intensity and is applied to the fields of light conversion films, photovoltaics and fluorescent materials, and has good application effects and application prospects.
[0050] The technical solution of the present invention is further described and illustrated according to various embodiments below. Unless otherwise specified, the parts described in the following embodiments are parts by weight.
[0051] Example 1
[0052] 100 parts of POE (190°C, 2.16Kg, melt index 5g / 10min) pellets, 0.5 parts of N-allyl-4-methoxy-1,8-naphthalimide and 0.1 parts of DCP were mixed in a mixer for 15 minutes, transferred to a twin-screw extruder, and melt-extruded at 150-190°C to obtain a blue light-converting resin.
[0053] Melt extrusion process: zone 1 temperature 50-60℃, zone 2 temperature 120-130℃, zone 3 temperature 150-160℃, zone 4 temperature 1670-170℃, zone 5 temperature 170-180℃, zone 6 temperature 180-190℃, zone 7 temperature 180-190℃, zone 8 temperature 180-190℃, zone 9 temperature 180-190℃, screw speed 30rpm, die temperature 180℃.
[0054] The N content in the photoconverter was tested using the elementar vario EL cube organic element analyzer. Since the N content in the blue light conversion resin of the present invention is relatively low, the result is relatively inaccurate when directly tested. During the test, 10% of the weight of the blue light conversion resin N-allyl-4-methoxy-1,8-naphthalimide was added to the blue light conversion resin, and the N content obtained by the test was deducted from the N content in the added N-allyl-4-methoxy-1,8-naphthalimide, that is, the N content in the blue light conversion resin. In this embodiment, the N content in the blue light conversion resin was measured to be 0.016wt%, and the grafting rate of N-allyl-4-methoxy-1,8-naphthalimide was calculated to be 0.31wt%.
[0055] Take 5 parts of the above blue light conversion resin and add them to 300 parts of toluene and stir until they are uniformly dissolved. The solution is put into 500 ml of acetone, and the precipitate is collected by filtration, washed with acetone 3 times, and then dried in an oven at 60°C overnight. The obtained solid continues to test the N content by the above method and calculates that the grafting rate of N-allyl-4-methoxy-1,8-naphthalimide is 0.30wt%. In the present invention, part of N-allyl-4-methoxy-1,8-naphthalimide is lost, which may be due to the high temperature of the melting section, but the N-allyl-4-methoxy-1,8-naphthalimide that is not lost basically participates in the grafting polymerization reaction.
[0056] Attached Figure 1 The fluorescence emission spectrum of the blue light-converting resin of this embodiment is shown in FIG. 1 . The fluorescence intensity at a wavelength of 400-450 nm is as high as 7.8×10 5 au. Figure 2 This is the UV-visible light transmittance spectrum of the blue light converting resin of this embodiment. The UV light transmittance in the range of 280-380nm is 16%.
[0057] Example 2
[0058] The difference between this embodiment and embodiment 1 is that in embodiment 1, the amount of N-allyl-4-methoxy-1,8-naphthalimide is adjusted from 0.5 parts to 0.3 parts, and the other steps remain unchanged. The grafting rate of the obtained blue light conversion resin is measured to be 0.22 wt%.
[0059] The fluorescence emission spectrum of the blue light-converting resin in this embodiment shows that the fluorescence intensity at a wavelength of 400-450 nm reaches a maximum of 3.1×10 5 au.
[0060] Example 3
[0061] 100 parts of POE (190°C, 2.16Kg, melt index 10g / 10min) particles, 0.5 parts of N-allyl-4-methoxy-1,8-naphthalimide and 0.1 parts of DCP were mixed in a mixer for 15 minutes, and then transferred to a twin-screw extruder together with 1 part of KH-570 silane coupling agent, and molded according to the melt extrusion process in Example 1 to obtain a blue light-converting resin. The grafting rate of N-allyl-4-methoxy-1,8-naphthalimide was measured to be 0.29% according to the test method in Example 1.
[0062] Attached Figure 3 The fluorescence emission spectrum of the blue light-converting resin of this embodiment is shown in FIG. 1 . The fluorescence intensity at a wavelength of 400-450 nm is as high as 5.3×10 5 au. Figure 4This is the UV-visible light transmittance spectrum of the blue light converting resin of this embodiment. The UV light transmittance in the range of 280-380nm is 18%.
[0063] Example 4
[0064] 100 parts of POE (190°C, 2.16Kg, melt index 30g / 10min) particles, 0.5 parts of N-allyl-4-methoxy-1,8-naphthalimide, 0.1 parts of DCP and 0.5 parts of polycarbodiimide were mixed in a mixer for 15 minutes, transferred to a twin-screw extruder, and molded according to the melt extrusion process in Example 1 to obtain a blue light-converting resin. The grafting rate of N-allyl-4-methoxy-1,8-naphthalimide was measured according to the test method in Example 1 to be 0.30%.
[0065] Attached Figure 5 The fluorescence emission spectrum of the blue light-converting resin of this embodiment is shown in FIG. 1 . The fluorescence intensity at a wavelength of 400-450 nm is as high as 4.6×10 5 au. Figure 6 This is the UV-visible light transmittance spectrum of the blue light converting resin of this embodiment, and the UV light transmittance in the range of 280-380nm is 1%.
[0066] Example 5
[0067] 100 parts of POE (190°C, 2.16Kg, melt index 12g / 10min) particles, 0.5 parts of N-allyl-4-methoxy-1,8-naphthalimide, 0.1 parts of DCP and 1 part of PEG-2000 were mixed in a mixer for 15 minutes, transferred to a twin-screw extruder, and molded according to the melt extrusion process in Example 1 to obtain a blue light-converting resin. The grafting rate of N-allyl-4-methoxy-1,8-naphthalimide was measured according to the test method in Example 1 to be 0.35%.
[0068] Attached Figure 7 The fluorescence emission spectrum of the blue light-converting resin of this embodiment is shown in FIG. 1 . The fluorescence intensity at a wavelength of 400-450 nm is as high as 4.6×10 5 au. Figure 8 This is the UV-visible light transmittance spectrum of the blue light converting resin of this embodiment. The UV light transmittance in the range of 280-380nm is 12%.
[0069] Example 6
[0070] The difference between this embodiment and embodiment 5 is that in embodiment 5, PEG-2000 is adjusted from 1 part to 0.6 parts, and the other steps remain unchanged. The grafting rate of the obtained blue light conversion resin is measured to be 0.23 wt%.
[0071] The fluorescence emission spectrum of the blue light-converting resin in this embodiment shows that the fluorescence intensity at a wavelength of 400-450 nm reaches a maximum of 3.5×10 5 au.
[0072] Example 7
[0073] The difference between this embodiment and embodiment 5 is that in embodiment 5, PEG-2000 is adjusted to PET-6000 of equal weight, and the other steps remain unchanged. The grafting rate of the obtained blue light conversion resin is measured to be 0.25 wt%.
[0074] The fluorescence emission spectrum of the blue light-converting resin in this embodiment shows that the fluorescence intensity at a wavelength of 400-450 nm reaches a maximum of 3.8×10 5 au.
[0075] Example 8
[0076] 100 parts of POE (190°C, 2.16Kg, melt index 5g / 10min) pellets, 0.2 parts of N-allyl-4-methoxy-1,8-naphthalimide and 0.1 parts of DCP were mixed in a mixer for 15min, transferred to a twin-screw extruder, and melt extruded according to the melt extrusion process of Example 1 to obtain a blue light-converting resin. The fluorescence intensity at a wavelength of 400-450nm was measured to be as high as 4.3×10 6 au.
[0077] Comparative Example 1
[0078] The fluorescence intensity of N-allyl-4-methoxy-1,8-naphthalimide was directly measured at a wavelength of 400-450 nm, with a maximum of 5.4×10 5 au.
[0079] As described above, the basic principles, main features and advantages of the present invention are shown and described. Those skilled in the art should understand that the present invention is not limited by the above embodiments, which are only preferred embodiments of the present invention and cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the scope of the present invention and the content of the specification should still be within the scope of the present invention. The scope of protection required by the present invention is defined by the attached claims and their equivalents.
Claims
1. A blue light conversion resin, characterized in that: The blue light conversion resin is N-allyl-4-methoxy-1,8-naphthalimide chemically bonded and grafted on polyolefin; The grafting rate of the N-allyl-4-methoxy-1,8-naphthalimide on the blue light conversion resin is 0.1-0.5wt%; The grafting rate is tested using an elementar vario EL cube organic element analyzer; The maximum fluorescence intensity of the blue light conversion resin in the wavelength range of 400-450nm is not less than 10 5 au; The fluorescence intensity was tested using the FLS1000 steady-state transient fluorescence spectrometer from Edinburgh Instruments, with an excitation wavelength of 380 nm, an excitation slit of 0.7 nm, an emission slit of 0.7 nm, detection every 1 nm, and a wavelength range of 390-800 nm.
2. The blue light conversion resin according to claim 1, characterized in that: The polyolefin has a melt index of 0.1-40 g / 10 min.
3. The blue light conversion resin according to claim 1, characterized in that: The ultraviolet light transmittance of the blue light converting resin within the wavelength range of 280-380nm does not exceed 20%.
4. The blue light conversion resin according to claim 1, characterized in that: The grafting rate is 0.15-0.5 wt %.
5. The blue light conversion resin according to claim 1, characterized in that: The blue light conversion resin further contains 0.3-1% of the weight of the blue light conversion resin.
6. The blue light conversion resin according to claim 1, characterized in that: The blue light conversion resin further contains polycarbodiimide accounting for 0.3-1% of the weight of the blue light conversion resin, and the ultraviolet light transmittance of the blue light conversion resin within the wavelength range of 280-380nm does not exceed 5%.
7. The blue light conversion resin according to claim 1, characterized in that: The blue light conversion resin further contains polyethylene glycol accounting for 0.5-2% of the weight of the blue light conversion resin, and the ultraviolet light transmittance of the blue light conversion resin within the wavelength range of 280-380nm does not exceed 15%.
8. A method for preparing a blue light conversion resin according to any one of claims 1 to 4, characterized in that: The N-allyl-4-methoxy-1,8-naphthalimide, the polyolefin and the free radical thermal initiator are uniformly mixed, added into a screw extruder for melt extrusion molding, and the blue light converting resin is obtained.
9. The method for preparing the blue light conversion resin according to claim 8, characterized in that: The melting section temperature of the melt extrusion molding is 140-230°C, and the die temperature is 150-200°C.
10. An application of the blue light conversion resin according to any one of claims 1 to 7 or the blue light conversion resin obtained by the preparation method of the blue light conversion resin according to claim 8 or 9, characterized in that: Applied to light conversion films, photovoltaic and fluorescent materials.
